Representing real time semantics for distributed application integration - Poon, P.; Dillon, Tharam S.; Chang, Elizabeth; Feng, L. (IEEE Computer Society Press, 2006)
Traditional real time system design and development are driven by technological requirements. With the ever growing complexity of requirements and the advances in software design, the alignment of focus has gradually been shifted to the perspective of business and industrial needs. This paper discusses a new paradigm in developing distributed real time system with the emphasis of knowledge representation and interoperability using XML. Real Time Markup Language (RTML) aims to provide a basis for interoperability.